A aquaponia: desafios e oportunidades para a produção de peixes e hortaliças no estado do Pará – Estudo de caso: projetos de aquaponia no município de Bragança-Pará - ARAÚJO, Cátia Sílvia Pereira de (Universidade Federal do Pará, 2020)
The present research about existing experiences of Aquaponics Systems in the State of Pará, municipality of Bragança. Among the main reasons for conducting the study was aim alternative paths to aquaculture activity in Brazil to meet the growing demand for healthy foods, mitigating the indiscriminate use of water resources and the lack of treatment and dumping inadequate effluent. In this sense, the aquaponic presents itself as an alternative to the integrated production of aquatic organisms (fish, crustaceans and algae) and vegetables with the benefit to save natural resources. The research aims General Aquaponics analysis, in the social and environmental context, from the studies and experiences that exist worldwide, national, as well as in the immediate region of Bragança, Pará State, with the purpose of drafting a guide for socialization and dissemination of aquapônica technology. Based on studies of the main bibliographic references on the aquaponic and the most important experiences of Aquaponics systems in the municipality of Bragança were analyzed by checking the theoretical and practical insights of those involved, and the potential and limitations of productive activity. For the preparation of the guide used the data provided in the bibliography, as well as those purchased on the spot. The results showed a bibliographic shortage issue in Brazil, mainly in respect of the economic viability of the activity, demonstrating clearly the necessity of deepening in the studies. The research showed that there is a strong tendency for membership of the local farmers to the aquapônico system of production, largely due to increasing income generation and low environmental impacts of this type of production.